Images of flight nursing in Australia: A study using institutional ethnography. (3rd August 2015) - Brideson, Genevieve; Willis, Eileen; Mayner, Lidia; Chamberlain, Diane J.
Abstract: Pictures speak a thousand words. The traditional romantic image of an Australian aeromedical service is a male doctor and male pilot, out to rescue the male stockman from the red dust of the Australian outback. However, the reality is considerably different, particularly in the current context of the Australian healthcare system. This paper examines the images of flight nursing using a critical lens. The images are derived from popular literature sources from the early 1940s through to the present. A textual analysis of the images of flight nursing using the methodology of institutional ethnography reveals a number of themes including the glamorous, the romantic, and the heroic nurse. This study illustrates that the way these nurses are portrayed within popular literature mirrors the Australian cultural ethic of heroic bush pioneer, yet at the same time the work these nurses do is undervalued by various omissions and misrepresentations. The results from this study have the potential to significantly improve recognition of the work performed by flight nurses and to challenge incorrect cultural myths.